Keynote Speaker to Participant Interaction in Online Webinar by Using Zoom Application - Dani, Ersika Puspita; Agustin, Angel; Deani, Eliza (Universitas Negeri Medan, 2023)
The objective of this descriptive qualitative study was to find out the keynote speaker to participant in online webinar by using zoom application. A keynote speaker has been conducted as a participant. To examine keynote speaker to participant, observation in zoom application were be used. The observation was be used to find out the keynote speaker™s interaction to participant. Then, the results were be analyzed to identify form of keynote speaker™s interaction. The results were 1) There were 3 forms of interaction used by keynote speaker to participant in online webinar, namely initiation move (I-Move), response move (R-Move), and Feedback Move (F-Move), and 2) The Initiation move (I-Move) was the most dominant interaction form used by keynote speaker to participant in online webinar and the least form was feedback move (F-Move).